Using tDCS to facilitate motor learning in speech production: The role of timing. (February 2019) - Buchwald, Adam; Calhoun, Holly; Rimikis, Stacey; Lowe, Mara Steinberg; Wellner, Rebecca; Edwards, Dylan J.
Abstract: There exists debate regarding the extent to which transcranial direct current stimulation (tDCS) can affect or enhance human behavior. Here, we examined a previously unexplored domain: speech motor learning. We investigated whether speech motor learning in unimpaired participants can be enhanced using a single-session tDCS experiment, and investigated whether the timing of tDCS relative to a behavioral task affected performance. Participants (N = 80) performed a twenty minute learning task with nonwords containing non-native consonant clusters (e.g., GD EEVOO), and were assigned to groups receiving either sham or active tDCS either immediately before or during the task. Both accuracy and properties of errors were examined throughout the course of the practice task, and then practice was compared to a retention period 30 min later (R1) and two days later (R2). For cluster and whole-(non)word accuracy measures, acquisition was observed for all groups during the practice session. Compared to the beginning of practice, the tDCS-Before group showed significantly greater improvement than both the sham group and the tDCS-During group at R1. An effect was also observed for vowel duration in errors (/gdivu/ → [gədivu]), with the tDCS-Before group showing significant shortening of vowel errors throughout practice. Overall, the findings suggest that tDCS can improve speech motor learning, and that the improvement may be greater when tDCS is applied immediately before practice, warranting further exploration of this new domain for tDCS research.